Interferência do uso dos bicos artificiais nos padrões de sucção e na amamentação - Batista, Christyann Lima Campos (2017)
Introduction: the relation of artificial nipples with breastfeeding remains controversial. Studies differ on the influence of pacifiers and bottle feeding and their influence on breastfeeding. Objective: To analyze the sucking patterns of infants known as nipple confusion and their relation to breastfeeding. Methods: a cross-sectional study that evaluated 429 infants, with a mean age of 33.2 ± 13.1 days, attending a child care program at the University Hospital of the Federal University of Maranhão between February and October 2016. The infants were evaluated in non-nutritive sucking (NNS) and nutritive sucking (NS) at rest in the maternal breast. The behavior of the feeding was also observed by applying the UNICEF Breastfeeding Observation Form. Multivariate logistic regression was used for association between the use of the nozzles and the NS and NNS patterns. In the observation of the feeding, multiple linear regression analysis was performed to investigate the association of variables. The significance level was 5% (p <0.05). Results: After the adjusted analysis, it was observed that primiparity, born in a private health unit, age less than 28 days, income higher than 5 minimum wages were factors risk of the use of artificial nipples. While receiving guidance on postpartum or pre-natal and postpartum breastfeeding were considered as protective factors. It was found that most of the alterations in the sucking pattern were associated with the use of artificial nipples, and pacifier use showed stronger associations with NNS changes, whereas the use of bottle presented stronger measures with alterations in NS. In breastfeeding observation, bottle feeding was associated with significant increases in negative behaviors for all five aspects of breastfeeding (β positive, P <0.05). And pacifier use was associated with increased negative behaviors observed for all aspects (β positive, P <0.05), performing breast anatomy (β = 0.08; P = 0.135). Conclusion: the use of pacifiers and bottle feeding was associated with incorrect sucking patterns and was expressed through an incorrect feeding, demonstrating the existence of nipple confusion. Early identification of difficulties in breastfeeding is essential to give the baby and mother the opportunity to enjoy all the benefits that breastfeeding promotes.